(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The study investigated the correlation between psychological hope and students’ entrepreneurial intentions. The sample comprised 305 students from five Federal Government-owned universities located in the Niger Delta region of Nigeria. A quasi-experimental research design was utilised, and data were collected through a cross-sectional survey methodology. Data analysis was conducted using the Pearson Product Moment Correlation Coefficient and Multiple Regression Analysis, employing the Statistical Package for Social Sciences (SPSS) Version 25. The results indicated a positive and statistically significant relationship between psychological hope and students’ entrepreneurial intentions within these universities. Specifically, the dimensions of students’ willpower (agency) and way power (pathways) were identified as significantly influencing their entrepreneurial intentions. In light of these findings, the study concludes that psychological hope is critical in enhancing students’ entrepreneurial intentions. The theoretical and managerial implications of these results are also discussed.